2014
DOI: 10.1007/s10973-014-4289-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural evidence of polymorphism and conformational isomorphism of a somewhat flexible molecule: m-anisic acid

Abstract: m-Anisic acid is generally recognized as a safe (GRAS) flavouring substance. Its GRAS status and the functional groups present in the molecule make it an interesting candidate for pharmaceutical co-crystallization studies. The knowledge of m-anisic acid crystalline structure/ polymorphic behaviour is important information for its applications. In this work, a crystalline structure of m-anisic acid form I, T fus = 105°C, was solved by X-ray diffraction: monoclinic, space group P2 1 /n, with a = 13.8075 (5) Å , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 39 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…142°C [10]. 1 The products were re-crystalized or distilled under reduced pressure. No impurities (greater than 0.001 mass fractions) could be detected in samples used for the before the thermochemical measurements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…142°C [10]. 1 The products were re-crystalized or distilled under reduced pressure. No impurities (greater than 0.001 mass fractions) could be detected in samples used for the before the thermochemical measurements.…”
Section: Methodsmentioning
confidence: 99%
“…They are used as flavoring substances and preservatives of fragrance in cosmetic formulations [1]. As some of them are natural products, they are good candidates for pharmaceutical co-crystals [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding research on conformationally flexible molecules, Garcia-Garibay et al evaluated the isomorphism of molecular rotors and showed that isomorphism arises from the closely isosteric relation that exists between hydrogen and fluorine atoms. Castro et al . applied a multidisciplinary approach and showed that the molecular flexibility of m -anisic acid results in the presence of two conformers in the unit cell.…”
Section: Introductionmentioning
confidence: 99%